(untitled) (Research, Society and Development, 2021)
This study aims to identify, in an analytical way, the relevance of critical thinking and its evaluation in higher education. For this purpose, we have considered an approach to the analysis of the conceptual content, which covers two aspects: attitudes or dispositions, and capacities or abilities. The latter seems to conform, in a systematic way, a rational and logical orderly process. This identification is essential to be able to properly support evaluation models that allow or contribute to the development of critical thinking in higher education students, which is essential for their professional and academic activities. This process is called “self-regulation”. In the introduction, an attempt is made to defend the essential need to promote and develop critical thinking in higher education students because it would constitute a vital element of academic activity. In the following section, the notions of critical thinking are addressed, breaking down its conceptual elements grouped into two dimensions: dispositions and skills or competences. Later, the evaluation of critical thinking is covered, explaining the essential rational activity in the academic context. Finally, the current challenges of higher education are presented, and the relevance of self-regulation is raised, which constitutes a culminating point of this rational process.